Investigating different options in course delivery – traditional vs online: is there another option?. Issue 4 (5th July 2018) - Hass, Ashley; Joseph, Mathew
Abstract : Purpose: The purpose of this paper is to examine students' perceptions of online vs traditional (face-to-face) course offerings at the business school of a liberal arts university in southwest USA. The research compares perceptions of students who have been subjected to online education along with those who have not been exposed to online education and examines likelihood to take online courses. Design/methodology/approach: Paper and pencil surveys were distributed in different classes in business classes at a university in southwest USA. The target group was undergraduate students. Findings: The results indicate that overall, students have neutral perceptions about online courses, while favorable perceptions are strongly associated with likelihood to take online courses. Moreover, prior exposure with online courses is not a significant factor in forming favorable perceptions about online courses. Research limitations/implications: The present research is limited in generalizability and the institution surveyed in the southwest region is new to online courses offering in their curriculum and not all the participants had prior experience with online courses. Originality/value: Although this paper compares online education with traditional, another option for methods of education include hybrid models incorporating both. A possible third option not discussed through this research is a hybrid or blended learning course, a combination of both online and traditional courses. This opens the options for the student, as hybrid courses can be built with many different options. One includes using technology for "screencasts" or lectures online.